Diet: the keystone of autism spectrum disorder?. (2nd December 2019) - Peretti, S.; Mariano, M.; Mazzocchetti, C.; Mazza, M.; Pino, M. C.; Verrotti Di Pianella, A.; Valenti, M.
Abstract : Children with autism are characterized by an impairment of social interaction and repetitive patterns of behaviour. Autism is a heterogeneous span of disorders with unknown aetiology. Research has grown significantly and has suggested that environmental risk factors acting during the prenatal period could influence the neurodevelopment of offspring. The literature suggests that the maternal diet during pregnancy has a fundamental role in the etiopathogenesis of autism. Indeed, a maternal diet that is high in some nutrients has been associated with an increase or reduction in the risk of develop Autism Spectrum Disorders (ASD). The diet of ASD children is also a key factor for the worsening of ASD symptoms. Children with autism have food selectivity and limited diets due to smell, taste, or other characteristics of foods. This determines eating routines and food intake patterns, with consequent deficiency or excess of some aliments. Several studies have tried to show a possible relationship between nutritional status and autism. In this review we describe, emphasizing the limits and benefits, the main current empirical studies that have examined the role of maternal diet during gestation and diet of ASD children as modifiable risk factors at the base of development or worsening of symptoms of autism